Switching to Aripiprazole as a Strategy for Weight Reduction: A Meta-Analysis in Patients Suffering from Schizophrenia - Yoram Barak; Dov Aizenberg (Journal of Obesity)
Weight gain is one of the major drawbacks associated with the pharmacological treatment of schizophrenia. Existing strategies for the prevention and treatment of obesity amongst these patients are disappointing. Switching the current antipsychotic to another that may favorably affect weight is not yet fully established in the psychiatric literature. This meta-analysis focused on switching to aripiprazole as it has a pharmacological and clinical profile that may result in an improved weight control. Nine publications from seven countries worldwide were analyzed. These encompassed 784 schizophrenia and schizoaffective patients, 473 (60%) men and 311 (40%) women, mean age 39.4±7.0 years. The major significant finding was a mean weight reduction by −2.55±1.5 kgs following the switch to aripiprazole (𝑃<.001). Switching to an antipsychotic with a lower propensity to induce weight gain needs be explored as a strategy. Our analysis suggests aripiprazole as a candidate for such a treatment strategy.